External Validation of the Endoscopic Features of Sessile Serrated Adenomas in Expert and Trainee Colonoscopists - Hyo-Joon Yang; Jeong In Lee; Soo-Kyung Park; Yoon Suk Jung; Jin Hee Sohn; Kyu Yong Choi; Dong Il Park (Korean Society of Gastrointestinal Endoscopy, 2017)
Background/Aims It is unclear whether the endoscopic features of sessile serrated adenomas (SSAs) would be useful to trainee colonoscopists to predict SSA. Therefore, the present study aimed to identify features that expert and trainee colonoscopists can use to independently and reliably predict SSA by using high-resolution white-light endoscopy. Methods Endoscopic images of 81 polyps (39 SSAs, 22 hyperplastic polyps, and 20 tubular adenomas) from 43 patients were retrospectively evaluated by 10 colonoscopists (four experts and six trainees). Eight endoscopic features of SSAs were assessed for each polyp. Results According to multivariable analysis, a mucous cap (odds ratio [OR], 10.44; 95% confidence interval [CI], 5.72 to 19.07), indistinctive borders (OR, 4.21; 95% CI, 2.74 to 7.16), dark spots (OR, 3.64; 95% CI, 1.89 to 7.00), and cloud-like surface (OR, 2.43; 95% CI, 1.27 to 4.668) were independent predictors of SSAs. Among these, a mucous cap, indistinctive borders, and cloud-like surface showed moderate interobserver agreement (mean κ >0.40) among experts and trainees. When ≥1 of the three predictors was observed, the sensitivity and specificity for diagnosing SSAs were 79.0% and 81.4%, respectively. Conclusions Colonoscopy trainees and experts can use several specific endoscopic features to independently and reliably predict SSAs.